'Massive potential' or 'safety risk'? Health worker views on telehealth in the care of older people and implications for successful normalization. Issue 1 (December 2016) - Shulver, Wendy; Killington, Maggie; Crotty, Maria
Abstract Background Telehealth technologies, which enable delivery of healthcare services at distance, offer promise for responding to the challenges created by an ageing population. However, successful implementation of telehealth into mainstream healthcare systems has been slow and fraught with failure. Understanding of frontline providers' experiences and attitudes regarding telehealth is a crucial aspect of successful implementation. This study aims to examine healthcare worker views on telehealth, and their implications for implementation to mainstream healthcare services for older people. The study includes a focus on two further dimensions of urban versus rural services and level of clinician experience with telehealth. Methods Seven semi-structured focus groups were conducted with a total of 44 healthcare workers providing services to older people in the areas of rehabilitation and allied health, residential aged care and palliative care. Focus groups included both telehealth experienced and inexperienced groups. Of the experienced groups, two provided services to both urban and rural patients, and two to rural patients. Inexperienced groups included one rural and two urban. Thematic analysis was undertaken to identify predominant themes. Between-group differences and agreement in viewpoints for each of these themes are discussed and mapped to the theoretical constructs of Normalization Process Theory. Results The views of participants varied with the extent of telehealth experience and perception of accessibility of healthcare services. Four themes describing clinician attitudes and perceptions that could impact on successful implementation of telehealth services are outlined: 1) Workability of telehealth: exponential growth in access or decay in the quality of healthcare? 2) What is an acceptable level of risk to patient safety with telehealth? 3) Shifting responsibilities and recalibrating the team; and 4) Change of architecture required to enable integration of telehealth service delivery. Conclusions The use of telehealth technologies to provide healthcare services to older people may be more readily normalized in areas where existing services are limited. Though exposure to telehealth may be a factor, changes to the perceived feasibility of telehealth in relation to conventional services, as well as supportive infrastructure and training and skill recalibration may be more critical to successful normalization of telehealth services for older people.